Bureaucratic Reform and its Impact on Public Service Transparency - Septo Pramesworo, Ignatius; Akbar, Sidderatul; Yumame, Jackson (International Journal of Social Science, Education, Communication and Economics, 2025)
This study aims to analyse the implementation of bureaucratic reform and its impact on public service transparency in Indonesia. Through a qualitative approach with a literature review, this study found that bureaucratic reforms carried out through organisational restructuring, simplification of procedures, strengthening human resources, and the use of information technology have encouraged the creation of more open and accountable public services. The digitisation of services and the public complaints system expanded public access to information and increased participation in service oversight. The results show that public service transparency has improved significantly, although challenges remain in terms of apparatus resistance and infrastructure limitations. Thus, bureaucratic reform plays an important role in realising governance that is transparent, efficient and responsive to the needs of society.